Models of thermal conduction and non-local transport of relevance to space physics with insights from laser–plasma theory - Arber, T. D.; Goffrey, T.; Ridgers, C. (Frontiers in Astronomy and Space Sciences, 2023)
Models of solar and space plasmas require an accurate model for thermal transport. The simplest such model is to assume that the fluid approach is valid and that local transport models can be used. These local transport coefficients are derived under the assumption that the electron mean-free path is “small” compared to the temperature scale length. When this approximation breaks down, non-local transport models or thermal flux limiters must be used to maintain a physically realistic model. This article will review the background theory of how small is “small” for the mean-free path and what options there are for including non-local transport within the fluid framework. Much of this recent work has been motivated by laser–plasma theory, where mean-free paths can be large and the Spitzer–Harm approach is never used.